Strongly aligned gas-phase molecules at free-electron lasers. (16th September 2015) - Kierspel, Thomas; Wiese, Joss; Mullins, Terry; Robinson, Joseph; Aquila, Andy; Barty, Anton; Bean, Richard; Boll, Rebecca; Boutet, Sébastien; Bucksbaum, Philip; Chapman, Henry N; Christensen, Lauge; et al.
Abstract: We demonstrate a novel experimental implementation to strongly align molecules at full repetition rates of free-electron lasers. We utilized the available in-house laser system at the coherent x-ray imaging beamline at the linac coherent light source. Chirped laser pulses, i.e., the direct output from the regenerative amplifier of the Ti:Sa chirped pulse amplification laser system, were used to strongly align 2, 5-diiodothiophene molecules in a molecular beam. The alignment laser pulses had pulse energies of a few mJ and a pulse duration of 94 ps. A degree of alignment of was measured, limited by the intrinsic temperature of the molecular beam rather than by the available laser system. With the general availability of synchronized chirped-pulse-amplified near-infrared laser systems at short-wavelength laser facilities, our approach allows for the universal preparation of molecules tightly fixed in space for experiments with x-ray pulses.